Discovery of non-substrate, environmentally sensitive turn-on fluorescent probes for imaging HDAC8 in tumor cells and tissue slices. (15th August 2022) - Huang, Chaoqun; Shu, Yi; Zhu, Yueyue; Liu, Hongjing; Wang, Xinzhi; Wen, Hongmei; Liu, Jian; Li, Wei
Graphical abstract: Highlights: Three novel non-substrate, environmentally sensitive turn-on HDAC8 fluorescent probes were designed, synthesized, and evaluated. The probes exhibited significantly enhanced fluorescence when binding into the cavity of HDAC8. The probe 19 could successfully image HDAC8 in neuroblastoma SH-SY5Y cells and SH-SY5Y tumor slices. Abstract: Histone deacetylase 8 (HDAC8) is overexpressed in multiple cancers and lack of effective chemical probes which could detect and visualize HDAC8 in tumor cells and tissues remains unsolved. In this work, three novel turn-on HDAC8 fluorescent probes 17 –19 derived from solvatochromic fluorophore 4-sulfamonyl-7-aminobenzoxadiazole (SBD) conjugating with a potent HDAC8 inhibitor PCI-34051 (IC50  = 10 nM) as the recognition group were fabricated. The probes exhibited much stronger fluorescence when they transfer from hydrophilic environment (Φ < 8%) to hydrophobic environment (Φ > 46%). Compared with PCI-34051 (KD  = 9.16 × 10 −6 M), probes 17 (KD  = 5.37 × 10 −6 M), 18 (KD  = 3.57 × 10 −6 M) and 19 (KD  = 8.89 × 10 −6 M) possessed slightly better affinity for HDAC8. Probe 19 was selected for cell imaging and it showed significantly enhanced fluorescence only after binding into the cavity of HDAC8 in SH-SY5Y and MDA-MB-231 tumor cells. Co-localization results demonstrated that HDAC8 is expressed in cytoplasm and nucleus. Furthermore, probe 19 was successfully utilized to distinguish the expression level of HDAC8 in SH-SY5Y tumor and normal tissue slices.